(untitled) (Journal of Nepal Geological Society, 2000)
The problem of aggregate and environment concerns the whole aggregate production comprising quarrying, crushing, sieving, transporting, and waste management. The most important primary environmental impacts are the influences on groundwater and the deterioration of the scenery. The secondary impacts include problems of aggregate production and land use planning near the quarries and crushing plants. Means to minimise primary environmental impacts include the change of raw material balance from the use of loose deposits instead of bedrock and the increase in reuse and recycling of aggregates. Determination of hydrogeological constraints and rehabilitation plans for land restitution help to exploit natural resources by taking into account the later use of the land surface for other purposes.